American Federalism in Practice : The Formulation and Implementation of Contemporary Health Policy - Michael Doonan (Brookings Institution Press, 2013)
This book is the result of more than a decade of exploration of intergovernmental relations and U.S. health care reform at the national and state levels. It has been influenced by my work in Congress, for federal government agencies, and with the states as well as by my academic work at the Heller School for Social Policy and Management at Brandeis University, the Politics Department at Brandeis, and the George Washington University. It is informed by a wide range of practitioners and academics who gave freely of their time, knowledge, and insight. The idea of studying federalism across the policy process came from discussions with and reviews by Jeff Prottas, Deborah Stone, and John McDonough, and this study has been influenced by the thinking of each of these individuals. My understanding of the historical roots of federalism within the broader institutional framework benefited from the guidance of Sid Milkis; notions of the trade-off between accountability and reliability came from a course that I took with Shep Melnick. The theories of federalism that underpin this work are based on seminal studies by Daniel Elazar, Samuel Beer, Martha Derthick, Timothy Conlan, Paul Peterson, and many others.